2010
DOI: 10.4236/cs.2010.11004
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Design of an Intra 16 × 16 Module for H.264/AVC Video Encoder

Abstract: In this paper, we propose novel hardware architecture for intra 16 × 16 module for the macroblock engine of a new video coding standard H.264. To reduce the cycle of intra prediction 16 × 16, transform/quantization, and inverse quantization/inverse transform of H.264, an advanced method for different operation is proposed. This architecture can process one macroblock in 208 cycles for all cases of macroblock type by processing 4 × 4 Hadamard transform and quantization during 16 × 16 prediction. This module was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results show that the proposed prediction technique enhances the compression ratio and the PSNR for the two HD videos. Seeking for a much more accurate judgment of the proposed prediction technique, we compared it with the hardware implementations of Bharathi and Nagabhushana [3], which used the Lena CIF video, and Loukil et al [25], which used the Foreman CIF video, as shown in Table 5. The comparison is performed in terms of PSNR only as the considered papers for comparison did not include information about compression ratio or bit rate.…”
Section: Performance Evaluation Of Our Proposed Approachmentioning
confidence: 99%
“…The results show that the proposed prediction technique enhances the compression ratio and the PSNR for the two HD videos. Seeking for a much more accurate judgment of the proposed prediction technique, we compared it with the hardware implementations of Bharathi and Nagabhushana [3], which used the Lena CIF video, and Loukil et al [25], which used the Foreman CIF video, as shown in Table 5. The comparison is performed in terms of PSNR only as the considered papers for comparison did not include information about compression ratio or bit rate.…”
Section: Performance Evaluation Of Our Proposed Approachmentioning
confidence: 99%